PRODUKSI BIOGAS DARI KOMBINASI KOTORAN KAMBING DAN LIMBAH IKAN DALAM BIODIGESTER ANAEROB - Okik Hendriyanto C; Sulthan Nafis Nabila (EnviroUS, 2021)
The reserves of fuel derived from fossil continue to decrease while the number of consumption increases, requiring replacement fuel. Biogas is an alternative fuel that can support daily activities and substitute fuels derived from fossils. Accumulation of fish waste at disposal in fish markets pollutes the environment and reduces environmental aesthetics. Anaerobic processing of fish waste is an efficient way because it contains protein, fat, and a high organic matter concentration. With a low C / N ratio value, fish waste must be mixed with livestock manure or green plants to produce more optimal methane gas. This study aims to determine how much methane gas content and the C/N ratio produced from a mixture of goat manure (GM) dan fish waste (FW). In this research, using a mixture of goat manure (GM) and fish waste (FW) 80:20; 60:40; 50:50; 40:60; 20:80, with variations in the fermentation time for 5 days, 10 days, 15 days, 20 days, and 25 days and using 19 liters of digester volume. The parameters analyzed included the C / N ratio, the percentage of methane gas content, and the flame. The results showed that the best biogas obtained in the KK: LI 80:20 mixture variation with a C / N ratio of 20.52% and resulted in a methane gas content of 54.81% and can light a fire for 24.7 seconds.